2020
DOI: 10.3390/nu12010184
|View full text |Cite|
|
Sign up to set email alerts
|

Attenuation of Weight Gain and Prevention of Associated Pathologies by Inhibiting SSAO

Abstract: Obesity is a worldwide prevalent metabolic disorder that is associated with diabetes, among many other diseases. Bearing this in mind, prevention and treatment ways need to be improved. Notably, activity of the enzyme semicarbazide-sensitive amine oxidase (SSAO) is found to be elevated in overweight subjects. Moreover, SSAO inhibition has resulted in an increase of histamine activity in adipose tissue and the limitation of body fat. The current review aims to overview the risks of obesity, rationalize the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 102 publications
(120 reference statements)
0
14
0
Order By: Relevance
“…This inhibition needs to be further explored in terms of adipocyte biology, since it has already been reported that tyramine influences lipid deposition, under both in vitro and in vivo conditions [55]. Another observation linking adipose tissue physiology and PrAO activity is that methylamine and benzylamine activate glucose transport in human adipocytes in a PrAO-dependent manner [43] and that PrAO inhibitors have been proposed as anti-obesity agents [18,56].…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition needs to be further explored in terms of adipocyte biology, since it has already been reported that tyramine influences lipid deposition, under both in vitro and in vivo conditions [55]. Another observation linking adipose tissue physiology and PrAO activity is that methylamine and benzylamine activate glucose transport in human adipocytes in a PrAO-dependent manner [43] and that PrAO inhibitors have been proposed as anti-obesity agents [18,56].…”
Section: Discussionmentioning
confidence: 99%
“…[ 66 ]. Thus, the scientists assumed that inhibiting SSAO activity will diminish the risks and complications in diabetes [ 38 ]. Certain natural compounds and elements discussed in this article and their impact on SSAO activity are given in Figure 2 .…”
Section: Why Is Semicarbazide-sensitive Amine Oxidase Activity Elementioning
confidence: 99%
“…SSAO inhibition may have a beneficial impact on creatine supplementation in diabetic patients. There are numbers of already well-known inhibitors capable to inhibit SSAO activity but most of them are toxic to some extent [ 38 ]. Interestingly, there are some natural compounds capable to lower increased SSAO activity.…”
Section: Introductionmentioning
confidence: 99%
“…Papukashvili et al [ 1 ] recently covered the enzyme semicarbazide-sensitive amine oxidase (SSAO) as a potential molecular target for the management of obesity and related diseases. While the paper is interesting, there are aspects which require clarification as it relates to caffeine.…”
mentioning
confidence: 99%